A three-dimensionally interconnected carbon nanotube/layered MoS2 nanohybrid network for lithium ion battery anode with superior rate capacity and long-cycle-life. (September 2015) - Li, Jianyang; Hou, Yang; Gao, Xianfeng; Guan, Dongsheng; Xie, Yuanyuan; Chen, Junhong; Yuan, Chris
Abstract: A three-dimensionally interconnected carbon nanotube/layered MoS2 nanohybrid network is reported with best-so-far rate capability and outstanding long cycle life as lithium ion battery anode. The monolayer and bilayer MoS2 ultrathin nanosheets with large surface to volume ratio facilitate fast Li ion transport further boosting high power capability, while incorporating high conductive CNT enhances the electronic conductivity and retains the structural integrity. The nanohybrid delivers discharge capacity as high as 512 mAh g −1 at 100 A g −1 and 1679 mAh g −1 over 425 cycles at 1 A g −1 with 96% discharge capacity retention of the initial cycle. Graphical abstract: A three-dimensionally interconnected carbon nanotube/layered MoS2 nanohybrid network exhibits best-so-far rate capability and outstanding long-cycle-life as lithium ion battery anode. Incorporating high conductive CNT not only enhances the electronic conductivity but also retains the structural integrity. The monolayer and bilayer MoS2 ultrathin nanosheets with large surface to volume ratio facilitate fast Li ion transport further boosting high power capability. Highlights: A three-dimensionally interconnected carbon nanotube/layered MoS2 nanohybrid network was successfully fabricated. The nanohybrid delivers discharge capacity as high as 512 mAh g −1 at 100 A g −1 . A discharge capacity retention of 96% was obtained at 1 A g −1 after 425 cycles.